Prevalence, and Genetics and Environmental Risk Factors of Myopia– Review - U.S. Mahadeva, Rao; Thant, Zin; Nordin, Simbak (Research Journal of Pharmacy and Technology, 2015)
In this modern age, short-sightedness is an ever growing problem faced by people all over the globe. The issues concerning this have been a major concern for the public, bringing the quality of life of an individual into question. Many factors has been considered in bringing about this problem, but the issue of justifying what causes it remains a subject that is still to be established. Short-sightedness is a common eye condition that causes distant objects to appear blurred, while close objects can be seen clearly. The medical term for short-sightedness is ‘myopia’. As the problem of short-sightedness is becoming a major issue, we are concerned with its effect towards the society. Children are robbed from the gift of clear vision, and those with ambitions for jobs that require good eyesight are barred from their life goals in life. This review will certainly paves path in identifying the factors that causes short-sightedness, and henceforth, this problem can be tackled comfortably for the betterment of the community.